Basic density and pulp yield relationship with some chemical parameters in eucalyptus trees - da Seca, Ana Maria Loureiro; Domingues, Fernando Manoel de Jesus (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the use of basic density and pulp yield correlations with some chemical parameters, in order to differentiate an homogeneous eucalyptus tree population, in terms of its potential for pulp production or some other technological applications. Basic density and kraft pulp yield were determined for 120 Eucalyptus globulus trees, and the values were plotted as frequency distributions. Homogenized samples from the first and fourth density quartiles and first and fourth yield quartiles were submitted to total phenols, total sugars and methoxyl group analysis. Syringyl/guaiacyl (S/G) and syringaldehyde/vanillin (S/V) ratios were determined on the kraft lignins from wood of the same quartiles. The results show the similarity between samples from high density and low yield quartiles, both with lower S/G (3.884.12) and S/V (3.994.09) ratios and higher total phenols (13.314.3 g gallic acid kg-1 ). Woods from the high yield quartile are statistically distinguished from all the others because of their higher S/G (5.15) and S/V (4.98) ratios and lower total phenols (8.7 g gallic acid kg-1 ). Methoxyl group and total sugars parameters are more adequate to distinguish wood samples with lower density.